Efforts to Improve Learning Outcomes Through the Use of Magic Box Media in Science Subjects for Fourth-Grade Students at Sd Negeri 37 Bengkulu City - Anggraeni, Shela; Apriani, Ria; Hotnida, Denny (Indonesian Journal of Pedagogy and Teacher Education, 2024)
This study aims to determine the significant impact of using the Magic Box media on the learning outcomes of fourth-grade students at SD Negeri 37 Bengkulu City. This research is a classroom action research conducted in two cycles. The subjects of this research were 28 fourth-grade students at SD Negeri 37 Bengkulu City. Data was collected through multiple-choice tests. The results of the study showed that the use of the Magic Box media improved learning outcomes in each cycle. The students' results increased from the pre-cycle, cycle I, and cycle II. In the pre-cycle, the student mastery percentage was 42.86%, or 12 students, in cycle I, it increased to 71.43%, or 20 students, and in cycle II, the mastery percentage significantly increased to 89.29%, or 25 students out of a total of 28 students. The research concluded that applying the Magic Box media could improve students' learning outcomes. Thus, the Magic Box media can enhance the learning outcomes of fourth-grade students at SD Negeri 37 Bengkulu City